Prediction Method of Cavitation Jet Wave Attenuation Based on Five-Equation Two-Fluid Model. (11th February 2020) - Fu, You; Xie, Zhaopeng; Zhao, Weiguo
Abstract : In this paper, the seven-equation two-fluid flow model is streamlined to a five-equation numerical calculation method. This method is applied to predict the wave attenuation of the cavitation jet. Compared with 9 different experimental schemes in two separate laboratories, it is found that the velocity flow characteristics are different from normal transient flow when the cavitation jet is formed in the pipeline. Such a difference in velocity flow characteristics will cause changes in the prediction deviation of pressure response time and amplitude. A numerical method for predicting the attenuation of pressure fluctuation with the cavitation jet is presented taken into account these flow characteristics. In this method, the unsteady friction model is opened after the jet wave transmits 3–5 cycles, and the cavitation jet wave attenuation is well simulated. This calculation method could provide a research basis for pipeline leakage, vibration, noise, and other fields that need accurate pressure signals.